Irish Crime Fiction - Cliff, Brian (Crime Files, 2018)
This book examines the recent expansion of Ireland's literary tradition to include home-grown crime fiction. It surveys the wave of books that use genre structures to explore specifically Irish issues such as the Troubles and the rise and fall of the Celtic Tiger, as well as Irish experiences of human trafficking, the supernatural, abortion, and civic corruption. These novels are as likely to address the national regulation of sexuality through institutions like the Magdalene Laundries as they are to follow serial killers through the American South or to trace international corporate conspiracies. This study includes chapters on Northern Irish crime fiction, novels set in the Republic, women protagonists, and transnational themes, and discusses Irish authors' adaptations of a well-loved genre and their effect on assumptions about the nature of Irish literature. It is a book for readers of crime fiction and Irish literature alike, illuminating the fertile intersections of the two.